Mulheres africanas no mundo Atlântico - Santos, Vanicléia Silva (Afro-Ásia, 2021)
Resenha de: CANDIDO, Mariana P.; JONES, Adam (orgs.). African Women in the Atlantic World: Property, Vulnerability & Mobility, 1660-1880. Woodbridge, UK: James Currey, 2019. 304 p.